The first macrofossil (Crinoidea: Cladida) from the Caples Terrane, Northland, North Island, New Zealand. Issue 4 (2nd October 2018) - Eagle, Michael K.; Hoskin, Liz; Hayward, Bruce W.
ABSTRACT: The systematic taxonomy, paleogeography, paleoecology, and paleoenvironment of the first macrofossil from the Caples Terrane in Northland and second Permian crinoid from New Zealand is described. Monobrachiocrinus waipapaensis n. sp. was collected as float material at the mouth of the Waipapa Gorge, Northland. Possible paleobiogeographic origins for the specimen are suggested and influence of the global distribution of Permian taxa pertinent to the New Zealand occurrence is discussed.